(untitled) (CIPEEX, 2022)
THE USE OF CONTRACEPTIVE METHODS CAN GENERATE SEVERAL REACTIONS TO WOMEN AND A LARGE PORTION OF THEM HAVE NO KNOWLEDGE ABOUT THE SUBJECT, NOT EVEN ABOUT THE DIFFERENCES BETWEEN CONTRACEPTIVE METHODS. THIS SYSTEMATIC REVIEW AIMS TO ANALYZE THE RISKS OFFERED, ESPECIALLY BY HORMONAL METHODS, TO WOMEN’S HEALTH AND WELL-BEING. STUDIES FROM THE PUBLIC/PUBLISHER MEDLINE (PUBMED) AND SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) DATABASES WERE INCLUDED, USING THE DESCRIPTORS: "HORMONAL CONTRACEPTIVE", "EFFECTS" AND "CONTRACEPTIVE HEALTH". THE RESULTS SHOWED THAT HORMONAL CONTRACEPTIVE METHODS CAUSE THE MOST SIDE EFFECTS IN PATIENTS. AMONG THESE SIDE EFFECTS WE CAN HIGHLIGHT: CHANGES IN MENSTRUAL FLOW, HEADACHE, DYSMENORRHEA, DECREASED LIBIDO, AND INCREASED RISK OF CARDIOVASCULAR DISEASES. IN ADDITION TO THIS, THE MAIN HORMONAL CONTRACEPTIVES ARE ORAL AND MOST OF THEM CONTAIN ETHINYL ESTRADIOL (E), PROGESTERONE, AND PROGESTERONE DERIVATIVES IN THEIR COMPOSITION, FOR CYCLE REGULATION AND NON-CONTRACEPTION, RESPECTIVELY. WITH THIS, IT IS CONCLUDED THAT THE USE OF CONTRACEPTIVE METHODS BRINGS SIDE EFFECTS FOR WOMEN, AND THEREFORE, IT IS NECESSARY TO DISSEMINATE THE INFORMATION PRESENTED SO THAT WOMEN CAN DECIDE WHICH METHOD IS BEST IN THEIR CASE.